Controversial Mathematical Issues : Problem Based Learning on Critical Thinking - I Putu Pasek Suryawan; Putu Kerti Nitiasih; Putu Nanci Riastini; I Gusti Putu Sudiarta (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to describe the study of controversial mathematical issues as problems that facilitate cognitive conflict and metacognitive knowledge. The research method used is a Systematic Literature Review with the process of identifying, assessing, and interpreting the available research facts, with the research object being a mathematical problem. The research design used was to summarize, review, and analyze 27 articles relevant to the research object in Sinta-accredited journals, indexed by Scopus and Web of Science. Then, these articles were analyzed using content analysis techniques. From the Systematic Literature Review, the results showed that controversial problems were different from metacognitive problems and the problems that facilitate cognitive conflict. These unique problems suit the mathematical problems’ criteria and support the application of Problem-Based Learning.